Dye-Sensitized Solar Cell Based on Polyaniline/Multiwalled Carbon Nanotubes Counter Electrode - Shaker Ebrahim; Moataz Soliman; M. Anas; Mostafa Hafez; Tarek M. Abdel-Fattah (International Journal of Photoenergy)
This work presented the successful fabrication of dye-sensitized solar cell using polyaniline base (EB), multiwalled carbon nanotubes (MWCNTs), organic dye (rhodamine B or riboflavin), zinc oxide (ZnO), and indium tin oxide (ITO). The electrical properties of the resultant devices were investigated by measuring the current density voltage (-), capacitance voltage (-), and impedance measurements under both dark and illuminated conditions. The photovoltaic cell characteristics, that is, open circuit voltage (), short circuit current density (), and energy conversion efficiency (), were evaluated under illumination and were found to be 0.48 mA/cm2, 400 mV, and 0.224%, respectively, for ITO/EB-MWCNTs/ZnO-rhodamine B/ITO heterostructure. Using impedance spectra, it was found that the series resistances of this type of solar cell are 62 and 60 Ω under darkness and illumination, respectively.